Inkulturasi Tradisi Lodong Me dalam Ungkapan Syukur Kelahiran Anak: Perspektif Adat Maumere-Sikka - Elisabeth Yecilda Woga; Intansakti Pius X; Emmeria Tarihoran (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Indonesia's cultural diversity demands a process of inculturation, in which local values ​​enter into dialogue with faith. This study examines the Lodong Me tradition in Sikka, East Nusa Tenggara, as a ritual of thanksgiving for birth that is essential and relevant amidst the challenges of modernity. The aim is to describe the meaning of Lodong Me and analyze its encounter with Christian faith through an inculturation approach. Using a qualitative approach with a case study design, data were collected through in-depth interviews with key informants and tested using source triangulation. The results show that Lodong Me is interpreted culturally and theologically as gratitude for divine grace, where gratitude to ancestors and God (Ama Pu) is placed in a harmonious arrangement. This ritual has been proven to meet the criteria for genuine adaptation because it has compatible values ​​(such as work ethic and responsibility to care for creation) and effectively strengthens the congregation's faith experience. By implication, this case study enriches the literature on inculturation in Indonesia and makes an important contribution to the Church's pastoral care in Sikka to prevent duality of belief.